INTEGRATING SUSTAINABLE ARCHITECTURE CONCEPTS IN THE DESIGN OF NATURE-BASED ELEMENTARY SCHOOLS - Nursyamsu, Lathifa; Merzelish, Merzelish; Pinassang, Jeanny Laurens (Fakultas Teknik, Universitas Riau Kepulauan, 2025)
The increasing urgency of environmental issues such as climate change has amplified the need for sustainability education, particularly at the elementary school level. This study explores the integration of sustainable architecture in the design of a nature-based elementary school located in Batam, Indonesia. The research aims to develop an environmentally responsive learning environment that supports both energy efficiency and active, experiential learning. A qualitative descriptive method was employed, involving site observation and documentation to assess environmental conditions, spatial needs, and design potentials. The proposed design incorporates key sustainable strategies, including passive solar orientation, natural lighting, cross-ventilation, and the use of eco-friendly materials such as bamboo and timber. Biophilic design elements—such as open-air classrooms, green courtyards, and educational gardens—are also integrated to enhance students’ connection to nature and support cognitive and emotional development. The findings demonstrate that sustainable and nature-based architectural approaches can reduce energy consumption, improve indoor comfort, and serve as a medium for teaching environmental values. While the design shows strong potential, the study acknowledges limitations in terms of implementation feasibility and scope. Future research is encouraged to include post-occupancy evaluations and interdisciplinary collaboration to further advance sustainable educational environments.